W poszukiwaniu wspólnego czasu. Ziemie bałtyjskie a Skandynawia we wczesnym okresie wędrówek ludów - Bitner-Wróblewska, Anna (Folia Praehistorica Posnaniensia, 2018)
Investigations concerning the mutual contacts between Scandinavia and the south-eastern Baltic zone in the Early Migration Period should be combined with careful chronological studies, otherwise it is not possible to point out the source of inspiration and the direction of contacts. A barrier limited such studies still remains the differences in chronological systems used by the researchers from both sides of the Baltic Sea. The author has proposed the synchronisation of Balt-Scandinavian chronology based on the most common phenomenon in Europe in the Early Migration Period, namely the stamp ornamentation. But instead of rather amorphous styles the horizons of certain artefacts decorated in these styles, Samland and Sosdala horizons, have been distinguished and analysed. The author established the relative chronological sequence of individual artefacts within the Sosdala and Samland horizons. There are three phases of each horizon. In absolute dating the beginning of horizons in question could be placed in the 2nd half of the 4lh c., while their ending in mid 5lh c. Basing on such a framework it was possible to establish the sequences of both Scandinavian and Balt artefacts correlated to each other. It was possible to distinguish six phases: phase 0 preceding the appearance of the Samland and Sosdala horizons, phases 1-3 synchronic with these horizons and phases 4—5 succeeding the horizons in question. The above sequence of phases may be fitted within the interregional chronological framework.